European registry of babies born to mothers with antiphospholipid syndrome. Issue 2 (15th May 2012) - Mekinian, Arsene; Lachassinne, Eric; Nicaise-Roland, Pascale; Carbillon, Lionel; Motta, Mario; Vicaut, Eric; Boinot, Catherine; Avcin, Tadej; Letoumelin, Philippe; De Carolis, Sara; Rovere-Querini, Patrizia; Lambert, Marc; et al.
Abstract : Objectives: This study aimed to describe the long-term outcome and immunological status of children born to mothers with antiphospholipid syndrome, to determine the factors responsible for childhood abnormalities, and to correlate the child's immunological profile with their mothers. Methods: A prospective follow-up of a European multicentre cohort was conducted. The follow-up consisted of clinical examination, growth data, neurodevelopmental milestones and antiphospholipid antibodies (APL) screening. Children were examined at 3, 9, 24 months and 5 years. Results: 134 children were analysed (female sex in 65 cases, birth weight 3000±500 g, height 48±3 cm). Sixteen per cent had a preterm birth (<37 weeks; n=22), and 14% weighted less than 2500 g at birth (n=19). Neonatal complications were noted in 18 cases (13%), with five infections (4%). During the 5-year follow-up, no thrombosis or systemic lupus erythematosus (SLE) was noted. Four children displayed behavioural abnormalities, which consisted of autism, hyperactive behaviour, feeding disorder with language delay and axial hypotony with psychomotor delay. At birth lupus anticoagulant was present in four (4%), anticardiolipin antibodies (ACL) IgG in 18 (16%), anti-β2 glycoprotein-I (anti-β2GPI) IgG/M in 16 (15%) and three (3%), respectively. ACL IgG and anti-β2GPI disappeared at 6 months in nine (17%) and nine (18%), whereas APL persisted in 10% of children. ACL and anti-β2GPI IgG were correlated with the same mother's antibodies before 6 months of age (p<0.05). Conclusion: Despite the presence of APL in children, thrombosis or SLE were not observed. The presence of neurodevelopmental abnormalities seems to be more important in these children, and could justify long-term follow-up.